Investments and long-term real interest rate in Poland. Study of investment structure, current account and their correlation with long-term real interest rates - Krawczyk, Jakub; Filipczak, Szymon (Economics and Business Review, 2015)
One of the effects of the globalization of financial markets is unhampered international capital flows that can be freely reallocated amongst different countries. Considering that the investor’s aim is to look for the most profitable investment opportunities, they have natural inducement to invest in emerging economies. Taking into account differences in the level of interest rates between Poland and developed economies we claim that the contribution of foreign capital in domestic investments decreases the cost of capital in Poland. The two main aims of this paper are to identifycrucial channels of foreign capital flows to Poland and to find out whether co-financing by foreign investment in Poland influences the domestic cost of capital (long-term real interest rate). Our findings, based on empirical analysis, appear to confirm that there is a connection between the structure of investors and the cost of capital.